Student-ledsustainability actions at Latin American universities: a case study from Chile - Mac-Lean Bravo, Claudia Alejandra; Isabella Villanueva; Jean Hugé (My University, 2021)
Sustainability integration processes within higher education institutions are diverse and context-specific, and can be initiated bottom-up or top-down. Student-led action can be fundamental for the transformation of higher education institutions towards sustainability. This study examines and characterises the scope of student-led action at higher education institutions in Latin America. We follow a two-track approach. We first focus on one in-depth case study: the University Students Sustainability Congress student initiative at the University of Chile. Secondly, we provide an explorative review of four student-led sustainability initiatives at universities in Argentina, Bolivia, Mexico, and Peru. The main findings indicate that: i. higher education institutions show a medium-high level of student involvement in the process of transformation towards sustainability; ii. the dominant activities of student-led initiatives are outreach-oriented, and iii. the scope of student-led sustainability initiatives can be at the university or at the city level.
Keywords: Outreach; Scope (computer science)